REVIEW PENYAKIT LAYU FUSARIUM DAN PENGENDALIANNYA PADA BAWANG MERAH (Alium escalonicum L.) - Manang, Aleksius Pongu Lima; Sutoyo, Sutoyo; Sumiati, Astri (Universitas Tribhuwana Tunggadewi, 2024)
This research aims to provide information about Fusarium oxysporum fungus attacks and their control. Several published research results show the severity of attacks is up to 80% and is economical. Fusarium oxysporum fungal infection occurs on the roots and tubers, due to root infection and tuber rot, discoloration, and necrosis of the base layer of the tuber. Furthermore, the fungal mycelium grows rapidly and an anomaly can be seen starting from the base of the tuber and spreading to the top and sides so that the stem grows longer, the leaves do not grow upright but curve, twist or become molten so that the plant wilts and ultimately the plant dies. Control using technical culture methods for cultivating healthy plants and crop rotation systems, using organic materials as a medium for anti-antagonistic microbes, applying the biological agent's Actinomycete, Streptomyces, Trichoderma gloeosporioides and exploiting the potential of anti-pathogenic microbes in the rhizosphere.